2018
DOI: 10.1371/journal.pmed.1002556
|View full text |Cite
|
Sign up to set email alerts
|

Impacts 2 years after a scalable early childhood development intervention to increase psychosocial stimulation in the home: A follow-up of a cluster randomised controlled trial in Colombia

Abstract: BackgroundPoor early childhood development (ECD) in low- and middle-income countries is a major concern. There are calls to universalise access to ECD interventions through integrating them into existing government services but little evidence on the medium- or long-term effects of such scalable models. We previously showed that a psychosocial stimulation (PS) intervention integrated into a cash transfer programme improved Colombian children’s cognition, receptive language, and home stimulation. In this follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 41 publications
(56 reference statements)
2
76
1
3
Order By: Relevance
“…Given this was the first evaluation of this model in India and given concerns that a lack of support for home visitors may have reduced the quality of visits in Colombia (Andrew et al, ), we invested heavily in home visitors' support and training. Mentors initially trained the home visitors for four weeks and then met with visitors weekly throughout the intervention and provided refresher trainings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this was the first evaluation of this model in India and given concerns that a lack of support for home visitors may have reduced the quality of visits in Colombia (Andrew et al, ), we invested heavily in home visitors' support and training. Mentors initially trained the home visitors for four weeks and then met with visitors weekly throughout the intervention and provided refresher trainings.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier trials of the tightly focused Jamaican home‐visiting model, Reach Up and Learn, found short‐term benefits to child development in Jamaica, Bangladesh and Colombia (see Grantham‐McGregor & Smith, for a recent overview). While in Colombia benefits had faded out after two years, in Jamaica effects were found well into adulthood (Andrew et al, ; Grantham‐McGregor & Smith, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the enthusiasm for early opportunities and for integrated interventions, there have been few evaluated trials or programs, illustrating the difficulties in scaling and sustainability (Grantham‐McGregor, Fernald, Kagawa, & Walker, ). For example, a recent follow‐up report from Colombia on a psychosocial intervention that had been successfully incorporated into a cash transfer program with positive effects on children's development and home environment at ages 2.5–3.5 years found no effects on children's cognition and behavior, or on the home environment at ages 4.5–5.5 years (Andrew, Attanasio, Fitzsimons, Grantham‐McGregor, Meghir, & Rubio‐Codina, ). These findings illustrate that implementation research and partnerships with implementing partners may be necessary to achieve lasting findings and to scale integrated interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the absence of an association between the home environment and infants' gross motor development may be the canalization that occurs during infancy as children are acquiring time-dependent developmental skills, such as gross motor skills (Fox, Levitt, & Nelson, 2010). The absence of a relationship between a nurturant home environment and inhibitory control over time among preschoolers was unexpected, based on findings that nurturant caregiving during infancy has been shown to be positively associated with executive functioning during children's preschool years (Bernier, Carlson, Deschênes, & Matte-Gagné, 2012). Skills in inhibitory control increased over time and were associated with children's height and anemia (which was adjusted in the analyses), suggesting a role linking nutritional status with inhibitory control.…”
Section: Nurturant Home Environmentmentioning
confidence: 99%